2019
DOI: 10.3390/infrastructures4020024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recovered Bitumen from Coarse and Fine Reclaimed Asphalt Pavement Particles

Abstract: In the current era of road construction, it is common to add a small amount of reclaimed asphalt pavement (RAP) in asphalt mixes without significantly changing properties such as stiffness and low-temperature cracking resistance. Not only can these mixes be better for the environment, but they can also improve certain properties like rutting resistance. However, there is no clear understanding of how RAP gradation and bitumen properties impact the mixture properties. In this study, a single RAP source was sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous research has shown that the bitumen recovered from coarse particles differ from fine particles [28]. They concluded that RAP bitumen participation in hot mix process significantly depends on RAP size.…”
Section: Infrastructures 2019 4 X For Peer Review 4 Of 23mentioning
confidence: 94%
“…Previous research has shown that the bitumen recovered from coarse particles differ from fine particles [28]. They concluded that RAP bitumen participation in hot mix process significantly depends on RAP size.…”
Section: Infrastructures 2019 4 X For Peer Review 4 Of 23mentioning
confidence: 94%
“…The gap-graded blending method was developed by the Huang et al ( 7 ), Shirodkar et al ( 12 ) and Yu et al ( 13 ). Although the aging degree of coarse and fine RAP binders is different ( 14 ), the mixtures consist of more fine RAP aggregate (0–4.75 mm) than coarse RAP aggregate (4.75–9.5 mm) for a single gradation of RAP micro-surfacing ( 5 ). Therefore, this method mixes a fine RAP mixture with coarse virgin aggregate and virgin binder so that it is easy to separate the RAP aggregate and virgin aggregate after mixing.…”
Section: Methodsmentioning
confidence: 99%
“…Recycled materials of different origins, such as construction and demolition waste [7][8][9][10][11][12][13], plastics [14][15][16][17][18][19][20], rubber [21][22][23][24][25][26], reclaimed asphalt [10,19,24,25,[27][28][29][30][31][32][33][34][35][36][37], and mineral sludge [38][39][40][41][42][43][44], have the potential for recycling in road pavement materials, making the performance of the corresponding mixtures in which they are employed comparable to those obtained with totally virgin components.…”
Section: Introductionmentioning
confidence: 99%